American Catholic Periodicals React to Nazism - Wentz, F. K. (Church history, 1962)
To probe the reaction of American Roman Catholics to the emergence of Nazism three periodicals were studied for the years 1933 to 1937. America was a well-edited Jesuit weekly with a circulation approximating thirty thousand. It was well-informed, detailed in its coverage of contemporary events, and wielded wide influence among Catholics in its approach to current affairs. The Brooklyn Tablet, weekly diocesan publication for Brooklyn in New York, had a newspaper format and a circulation approaching fifty thousand. Commonweal was edited independently by Catholic laymen and was more influential than its circulation of about twenty thousand would indicate.